Trình độ kiến thức thông tin của sinh viên đại học ở Việt Nam - Trương, Đại Lượng (2021)
Presents results of an investigation into information literacy level of students at 6 universities in Vietnam; puts forward some remarks and recommendations on improv- ing the quality of information literacy development among students.